Memediasi dan Memfasilitasi Prosedur Penyelesaian dan Resolusi Konflik - Siregar, Nanda Asrida (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
Review the conflict, which is communication. The emergence of this dispute is related to differences in everyday life, such as differences in gender, social and economic strata, ideology, beliefs, legal systems, ethnic groups, religions, cultures, and political schools. As long as differences still exist, conflict is inevitable in social life. However, this does not mean that conflict cannot be resolved. Conflict resolution is one solution, citing Christopher E. Miller's book, A Dictionary of Terms and Concepts in Peace and Conflict Studies, as one approach; Conflict resolution is a step or process of resolving conflict through a constructive problem-solving system. In relation to this, it is necessary to understand and explain the meaning, history and characteristics. Furthermore, conflict resolution can also be interpreted as an effort to achieve the final result of a conflict through conflict resolution methods. The main goal of conflict resolution is to achieve peace. In this case, the role of the mediator will be very useful and give meaning to participation in resolving the conflict and achieving.